Using high-throughput sequencing of 16S rDNA technique to analyze the features of intestinal microbiota in individuals with herpes zoster - DENG Xiaoyue; WANG Weizhen; ZHANG Yingzheng (Pifu-xingbing zhenliaoxue zazhi)
[Objective] To analyze the differences of diversity, structure, and abundance in the intestinal microbiota between patients with herpes zoster (HZ) and healthy individuals using high-throughput sequencing of 16S rDNA, and to determine the relationship between herpes zoster and the intestinal microbiota. [Methods] Thirty patients with herpes zoster were enrolled from the Pain Department of Jiangyin Hospital of Traditional Chinese Medicine from January 2022 to December 2023 (HZ group). Thirty healthy individuals served as the control group (HC group). Total bacterial DNA was extracted from fecal samples, and the V3-V4 hypervariable region of the 16S rDNA-coding gene was amplified for sequencing. The differences in the intestinal microbiota were compared between the two groups. [Results] The richness and diversity of the intestinal microbiota in the HZ group were significantly lower than those in the HC group. At the phylum level, the relative abundance of Firmicutes was lower (P=0.014), while Proteobacteria was higher in the HZ group compared to the HC group (P=0.002). At the genus level, the relative abundances of Escherichia-Shigella (P=0.004), Klebsiella (P=0.030), and Lactobacillus (P=0.013) were higher, while abundance of Faecalibacterium (P=0.003) and Eubacterium_hallii_group (P=0.013) were lower in the HZ group than in the HC group. [Conclusions] There are significant differences in the species, functional structure, and abundance of the intestinal microbiota between patients with herpes zoster and healthy individuals. It suggests that specific bacterial types and their functions in the intestinal microbiota may play a crucial role in the pathogenesis of herpes zoster virus infection.